Discoloration in the marine red algae Pyropia: causative factors and exploiting the biotechnological potential of a waste resource. (18th September 2020) - Cho, Kichul; Heo, Jina; Lee, Sang‐Moo; Han, Jinwook; Hong, Hyun Dae; Jeon, Hancheol; Hwang, Hyun‐Ju; Baek, Kyunghwa; Han, Jong Won
Abstract: Pyropia ( Porphyra, referred to as 'Gim' in Korea or 'Nori' in Japan), an economically valuable alga, has long been consumed as seafood, especially in north‐east Asian countries. Its well‐established conventional mass cultivation and harvesting methods in coastal areas widen the industrial availability of edible Pyropia sp. However, the unexpected discoloration derived from causative factors during the cultivation process gives rise to serious economic losses in the aquaculture industry. For the industrial use of discoloured laver waste (DLW), recent articles have suggested that DLW biomass could be used as a source of agar polysaccharide, porphyran, γ‐aminobutyric acid and other value‐added bioactive compound productions. Although DLW biomass has economic potential, the lack of integrated information and relevant studies still limits its industrial availability. Therefore, we discussed recent research concerning the functional ingredients, causative factors and potential availability of DLW to provide integrated information. Furthermore, this review suggested the potential industrial application of DLW as a source for other value‐added material production.